Enhancing pedagogical content knowledge of preservice science teacher students through the inquiry reflective teaching model - Susilowati, Susilowati; Suciati, Suciati; Saputro, Sulistyo; Muzzazinah, Muzzazinah (Jurnal Cakrawala Pendidikan, 2025)
Reflecting the substance of the Preservice science teachers must have the ability to teach science appropriately. This ability is related to pedagogical and content knowledge. Teaching with inquiry is important in the development process of teacher professionalism. This is an urgency for preservice science teacher students to be equipped with teaching skills inquiry and the ability to reflect in learning. This research aimed to analyze the validity and practicality of the developed Inquiry Reflective Teaching (IRT) model; and to find the effectiveness of the IRT model in improving PCK. This study used the Research and Development (R&D) method. The data collection techniques used were IRT model assessment, practicality questionnaire, and Pedagogical Content Knowledge test. The data were analyzed using quantitative and qualitative analysis techniques. Quantitative data analysis techniques were used to determine the validity and practicality categories of the IRT model. Qualitative data analysis techniques were utilized to analyze data in the form of suggestions from experts, practitioner lecturers, and preservice science teacher students. The results of this study showed that the validity assessment was in a ‘very valid’ category. Likewise, the results of the assessment of the practicality of the IRT model were categorized as ‘very practical’. The IRT model can effectively improve the PCK of preservice science teachers.